2019
DOI: 10.3389/fonc.2019.00554
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Confocal Laser Endomicroscopy for Neurosurgery and Technical Nuances for Brain Tumor Imaging With Fluorescein

Abstract: Background: Previous studies showed that confocal laser endomicroscopy (CLE) images of brain tumors acquired by a first-generation (Gen1) CLE system using fluorescein sodium (FNa) contrast yielded a diagnostic accuracy similar to frozen surgical sections and histologic analysis. We investigated performance improvements of a second-generation (Gen2) CLE system designed specifically for neurosurgical use. Methods: Rodent glioma models were used for in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 50 publications
2
50
0
2
Order By: Relevance
“…With this study we were also interested in categorizing some morphological patterns: cellular features and tumor structures, such as pleomorphism, atypia, hypercellularity, and neovascularization appeared to correlate with the matched permanent sections and known tissue architecture. Although quality of images was not as good as the one shown in the paper by Belykh and colleagues (15), CONVIVO ® ex vivo scanning permitted to clearly identify GBM tissue during surgery, leading to an intraoperative correct diagnosis in a high percentage of cases, fulfilling the primary objective in such study. As a matter of fact, our protocol permitted to the pathologist to analyze CONVIVO ® tissue samples in a blinded manner, never knowing anticipately the results from permanent or frozen section images.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…With this study we were also interested in categorizing some morphological patterns: cellular features and tumor structures, such as pleomorphism, atypia, hypercellularity, and neovascularization appeared to correlate with the matched permanent sections and known tissue architecture. Although quality of images was not as good as the one shown in the paper by Belykh and colleagues (15), CONVIVO ® ex vivo scanning permitted to clearly identify GBM tissue during surgery, leading to an intraoperative correct diagnosis in a high percentage of cases, fulfilling the primary objective in such study. As a matter of fact, our protocol permitted to the pathologist to analyze CONVIVO ® tissue samples in a blinded manner, never knowing anticipately the results from permanent or frozen section images.…”
Section: Discussionmentioning
confidence: 93%
“…This limitation could be partially overcome by a totally in vivo setting, which needs a dedicated sterile sheath covering the CONVIVO ® probe, allowing for a direct tumor bed analysis, surely much closer to the SF injection time. As a matter of fact, in previous in vivo published series, performed with other confocal prototypes, or with CONVIVO ® system only in animals (15,19), the quality of the image related to the improved background fluorescence, is much higher. In addition, other authors suggested to use different protocols of SF injection, right before in vivo CLE analysis, with an impact on image quality (6,13).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wide-field fluorescence imaging relies on visualization of unspecific metabolic or targeted fluorescent molecular probes as discussed above; this imaging technique is advantageous for margin detection. Confocal imaging involves a point-scanning excitation laser and a pinhole aperture that filters out-of-focus detected light that allows pixel-by-pixel en face imaging of tissue at a certain depth with submicron resolution [ 35 ]. Various technologies that employ the confocal principle include confocal reflectance microscopy, which relies on the detection of reflected excitation light, and confocal fluorescence microscopy, which relies on the detection of a fluorescence signal of specific wavelengths emitted by a fluorophore.…”
Section: Discussionmentioning
confidence: 99%
“…FLS-guided resection of high-grade glioma was successful in a recent Phase II clinical trial (n = 46 patients) (234) and in a prospective observational study (n = 279 patients) (78), indicating its clinical applicability. FLS has also been used as a contrast for intraoperative assessment of tissue microstructure using confocal laser endomicroscopy (235,236).…”
Section: Fluorescein Sodiummentioning
confidence: 99%